Creating analogical models to help students learn concepts and prevent misconceptions about battery charging systems in cars and motorcycles - Muhamad Amiruddin; Sidiq Supriyanto; Abdullah Syafiq (Jurnal Taman Vokasi, 2025)
This study aims to develop an analogy-based learning model following the FAR (Focus, Action, Reflection) principles to explain the working mechanism of battery charging systems in cars and motorcycles, and to prevent student misconceptions. The research employed a Research and Development (R&D) approach, involving design, validation, and evaluation stages. The analogy used was adapted from a household water pump system to illustrate the battery charging process. Data were collected from automotive lecturers and vocational teachers through structured assessments of the analogy mapping. The results indicate that most respondents agreed with the analogy mapping, with no misconceptions identified. The structure and function of the analogies were rated convincing, scoring 90 for both motorcycle and car charging systems. Concept comprehension scores were 85 for motorcycles and 80 for cars, while analogy acceptance scored 100 and 90 respectively. The findings imply that structured FAR analogies can enhance student understanding of abstract electrical concepts, reduce the risk of misconceptions, and provide a practical instructional strategy for vocational automotive education.